FORMALIZATION OF MINIMUM POWER CONSUMPTION CRITERION FOR CRUSHING UNIT - M. Y. Shpurgalova (Наука и техника)
Analytical expressions describing dependence between basic parameters of potash ore crushing process have been constructed in the paper. While taking in account the generality of the Kirpichev formula some corrections have been made for direct applicability of the given hypothesis in calculation of energy which is required for crushing of potash ore specimen. Such approach makes it possible to consider not only general averaged size of specimens but percentage content of every concrete specimen of the specified dimensions. While investigating potash ore composition of the prescribed volume it has been established that every component contained in the specimen composition has its tensile strength and elastic modulus. In addition to this it has been demonstrated the percentage content of components in potash ore composition (sylvinite, halite and insoluble residue) is different.It has been experimentally determined that the selected volume of the material (2 м3) supplied for benefication and the final product have normal distribution of ore pieces, it means that number of averaged size pieces is higher than pieces of minimum and maximum sizes. An expression has been obtained on the basis of the executed investigations and formula that corresponds to the Kirpichev hypothesis. The expression makes it possible to calculate energy required for crushing of the specified volume of potash ore. In this case chemical composition and percentage content of components included in the potash ore have been taken into account. The energy required for crushing of the potash ore volume consists of total sum of energy used for crushing of separate components included in chemical composition of potash ore and this sum is multiplied by percentage content of corresponding substance.